Penanggulangan Kejahatan dengan Pidana Badan di Indonesia - Adi Hermansyah (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Nowadays, crime has increased very significantly. The increase is not only on its quantity but also on its quality. Punishment as the last “mean” in preventing and overcoming crime is supposed to function maximally in order to protect society from perpetrators. The function of criminal law is really influenced by characteristic of society where the law enforced. Moreover, the application of proper punishment as a mean of preventing crime is also influenced by the increase and the decrease of crime numbers and also has impact on the society welfare. Punishment towards body is a kind of punishment that is still applied by many states including Indonesia. The regulation of such crime as one of the crimes in Indonesia Indonesia legal system is really possible to prevent crime in terms of restoring national legal system to replace KUHP (Criminal Code of Indonesia) as colonial legacy that is not proper to society characteristics in Indonesia and the period.  Crime Prevention by Physical Punishment in Indonesia